Narrative Gerontology: Countering the Master Narratives of Aging - de Medeiros, Kate (Narrative Works)

(untitled) (The University of New Brunswick, 2016)
Narrative approaches to understanding later life are increasingly being used within gerontology, albeit in limited ways. These limits include the number and types of narratives that “count” as knowledge or data as well as narrowly applied methods for analysis and interpretation. Within the gerontology field, the overriding assumption is still one that presumes that the stories we tell are the stories we are. Still missing are critical questions of whether dominant narrative approaches in the field truly give voice to the experience or instead perpetuate master narratives of later life. If so, what counter narratives are available? For example, in oral interviews, there is often little consideration given to the context in which the narratives unfold. In written narratives, the almost exclusive use of the first-person memoir format shapes what stories are voiced and which are silenced. In this paper, I draw from my own research within narrative gerontology to illustrate some of the challenges with how narratives are elicited, analyzed, and interpreted within the field in both oral and written approaches and suggest directions for future narrative work.